Kajian Linguistik Kognitif Pada Imbuhan Ber- dalam Bahasa Indonesia - Riki Nasrullah; Arip Budiman (Ranah: Jurnal Kajian Bahasa, 2022)
Academic discourse on beR- affixes in Indonesian has been widely studied and analyzed. Generally, the studies only focus on three main valences: form, structure, and meaning. In its development, cognitive linguistics can be another alternative to examine beR- affixes in Indonesian by looking at the symptoms of expanding their meaning. By basing on the theory of categorization of prototype meanings and expansion meanings, cognitive linguistics is felt to be able to answer problems that often arise in the realm of beR- meaning meanings that tend to overlap. The results of this study suggest that cognitive linguistics can be an alternative study to fill the gaps in the study of beR- affixes in Indonesian. From the perspective of cognitive linguistics, the meanings present in the beR affix can be said to have expansion symptoms. The categorization analysis can see this of the meaning of the prototype and the meaning of its expansion. The prototype meaning of ¬beR- is mainly "doing something" with five types: holding something, acquiring something, and untransitive, reflexive, and reciprocal deeds. The meaning of the expansion is only identified four types: owning, wearing, state, and number. AbstrakWacana akademik tentang imbuhan beR- dalam bahasa Indonesia sejatinya telah banyak dikaji dan dianalisis. Umumnya, kajian yang dilakukan hanya berkutat pada tiga valensi utama, yakni bentuk, struktur, dan makna. Pada perkembangannya, linguistik kognitif bisa menjadi alternatif lain untuk mengkaji imbuhan beR- dalam bahasa Indonesia dengan melihat gejala perluasan maknanya. Linguistik kognitif dengan mendasarkan pada teori kategorisasi makna prototipe dan makna perluasan dirasa mampu menjawab persoalan yang kerap muncul pada ranah makna imbuhan beR- yang cenderung tumpang-tindih. Hasil kajian ini menunjukkan bahwa linguistik kognitif bisa menjadi alternatif kajian untuk mengisi rumpang kekosongan pada kajian imbuhan beR- dalam bahasa Indonesia. Ditilik dari perspektif linguistik kognitif, makna-makna yang ada pada imbuhan beR- bisa dikatakan mengalami gejala perluasan. Hal ini bisa telihat dengan adanya analisis kategoriasi pada makna prototipe dan makna perluasannya. Makna prototipe imbuhan beR- berdomain utama “melakukan sesuatu” dengan lima jenis, yakni mengadakan sesuatu, memperoleh sesuatu, perbuatan taktransitif, refleksif, dan resiprok. Adapun makna perluasannya hanya teridentifikasi empat jenis, yakni memiliki, memakai, keadaan, dan jumlah.